2019
DOI: 10.4163/jnh.2019.52.1.17
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Lonicera caerulea extract on adipocyte differentiation and adipogenesis in 3T3-L1 cells and mouse adipose-derived stem cells (MADSCs)

Abstract: Purpose: Obesity is a major health problem of global significance because it is clearly associated with an increased risk of health problems, such as nonalcoholic fatty liver disease (NAFLD), diabetes, cardiovascular diseases, and cancer. Lonicera caerulea (LC) originates from high mountains or wet areas and has been used as a traditional medicine in northern Russia, China, and Japan. LC contains a range of bioactive constituents, such as vitamins, minerals, and polyphenols. This study examined the anti-obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
1
1
Order By: Relevance
“…Another study found that the content of the anthocyanins from the BH ranged from 1.16 to 5.93 mg/g, and the C3G was the major one, which occupied 79-88% (10). The previous reports did not show a significant decrease on the cells viability in the BH treatment up to 1,000 μg/mL (19), which is similar to our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another study found that the content of the anthocyanins from the BH ranged from 1.16 to 5.93 mg/g, and the C3G was the major one, which occupied 79-88% (10). The previous reports did not show a significant decrease on the cells viability in the BH treatment up to 1,000 μg/mL (19), which is similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…According to the previous reports, the triglyceride accumulation was reduced to 77.42% in the 1% BH supplemented group of the HFD-induced obese mice, but the results for the free glycerol study could not be found (19). The results from the current study indicated that the treatment of the BH did not induce the lipolysis, but it inhibited the adipogenesis.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation